Measurements of the Nuclear Modification Factor for Jets in Pb+Pb Collisions at √sNN =2.76 TeV with the ATLAS Detector - Alconada Verzini, María Josefina (2015)
Measurements of inclusive jet production are performed in pp and Pb+Pb collisions at √sNN=2.76 TeV with the ATLAS detector at the LHC, corresponding to integrated luminosities of 4.0 and 0.14 nb-1, respectively. The jets are identified with the anti-kt algorithm with R=0.4, and the spectra are measured over the kinematic range of jet transverse momentum 32<pT<500 GeV and absolute rapidity |y|<2.1 and as a function of collision centrality. The nuclear modification factor RAA is evaluated, and jets are found to be suppressed by approximately a factor of 2 in central collisions compared to pp collisions. The RAA shows a slight increase with pT and no significant variation with rapidity.